Optimized inhibited-coupling Kagome fibers at Yb-Nd:Yag (8.5 dB/km) and Ti:Sa (30 dB/km) ranges - Maurel, Martin; Chafer, Matthieu; Amsanpally, Abhilash; Adnan, Muhammad; Amrani, Foued; Debord, Benoit; Vincetti, Luca; Gérôme, Frédéric; Benabid, Fetah (Optics letters, 2018)
We report on the development of hypocycloid core-contour inhibited-coupling (IC) Kagome hollow-core photonic crystal fibers (HC-PCFs) with record transmission loss and spectral coverage that include the common industrial laser wavelengths. Using the scaling of the confinement loss with the core-contour negative curvature and the silica strut thickness, we fabricated an IC Kagome HC-PCF for Yb and Nd:Yag laser guidance with record loss level of 8.5 dB/km associated with a 225-nm-wide 3-dB bandwidth. A second HC-PCF is fabricated with reduced silica strut thickness while keeping the hypocycloid core contour. It exhibits a fundamental transmission window spanning down to the Ti:Sa spectral range and a loss figure of 30 dB/km at 750 nm. The fibers' modal properties and bending sensitivity show these HC-PCFs to be ideal for ultralow-loss, flexible, and robust laser beam delivery.